Mobile Phones and Economic Development in Rural Peru - Beuermann, Diether W.; McKelvey, Christopher; Vakis, Renos (Taylor and Francis, 2013)
We estimate the effects of mobile phone coverage on different measures of economic development. We exploit the timing of mobile coverage at the village level merging it with a village-level panel dataset for rural Peru. The main findings suggest that mobile phone expansion has increased household real consumption by 11 per cent, reduced poverty incidence by 8 percentage points and decreased extreme poverty by 5.4 percentage points. Moreover, those benefits appear to be shared by all covered households regardless of mobile ownership.